"It would be impossible to estimate the value of these works..." Mass Production at Springfield Armory during the American Civil War. (2nd January 2017) - Raber, Michael
Abstract : The U.S. Armory in Springfield, Massachusetts, rarely appears in Civil War histories except perhaps as an unexplained statistical wonder. By late 1863, the Armory was the largest single supplier of rifles to Union forces. Springfield Armory workers out-produced over thirty American contractors, making more Army rifles at less cost while providing contractors with gauges, inspectors, and models, even though there were significant wartime private-sector mechanical innovations. This article identifies and explains the factors in the Armory's success, provides context on contemporary American arms production and rifle models, and argues that the Armory's methods and performance were among the first if not the first example of mass production in American small arms manufacture. The relative brevity of the Civil War episode, and the fact that it was not repeated in any comparable way at the Armory until World War II, has obscured its significance in American manufacturing history.